A Note on Pure Submodule Relative to Submodule - Ali, Muna Jasim Mohammed; Al-Hassani, Uhood S; Mohammed, Zahraa A (Al-Nahrain Journal of Science, 2013)
In this paper we used the concept of a pure submodule relative to submodule T in two concepts, pure relative to submodule T Baer injective modules and module with pure relative to submodule T intersection property. Some properties and some characterization of this notions are established.